Influence of electron irradiation on the crystalstructure, surface microrelief and bandganp width of the triple crystals of iron doped monoselinide of thallium and indium - Nuritdinov, I.; Tashmetov, M.Yu.; Khodzhaev, U.O.; Umarov, S.Kh.; Khallokov, F.K. (Karaganda University named after academician E.A.Buketov, 2023)
In this work, the effect of electron irradiation on the structure, surface morphology and band gap of singleand polycrystals of iron-doped ternary crystals of thallium and indium monoselinides was investigated. It has been established that the synthesized polycrystalline samples, as well as the grown single crystals of thallium and indium monoselinides, are single-phase. The crystals have a tetragonal unit cell (space group I4/mcm) with the following lattice parameters: a ~ b = 8.12 Å, c = 6.88 Å, α=β=γ = 90°. Irradiation with electrons with an energy of 2 MeV and a beam current density of 0.085 μA/cm2 leads to changes in the structure and properties of crystals in a complex manner depending on the electron fluence. Leads to a change in the parameters of the crystal lattice, an increase in the maximum value of the arithmetic mean deviation of the profile, as well as a decrease in the height of the average surface roughness of the irradiated crystals. Irradiation of a powder sample with electrons with a fluence of 5x1016 electron/cm2 helps to increase the size of nanocrystallites from 32.50 nm to 43.33 nm.
Keywords: single crystal; crystal structure; unit cell; space group; electron irradiation; fluence; crystallite size; roughness